Sekularisasi Praktik Mindfulness di Barat: Dari Spiritual ke Psikologi Klinis - Madiyono (PATISAMBHIDA : Jurnal Pemikiran Buddha dan Filsafat Agama, 2025)
Abstract Mindfulness is an exceptionally popular meditation practice in the contemporary Western era. However, contemporary Mindfulness practice differs in focus and objective from its original introduction by the Buddha in the past. This article delineates the process of transformation of Mindfulness practice from its historical origins to its popularized form in the West, particularly from the 20th century onward. This study employs a literature review based on various primary and secondary sources concerning Mindfulness practice. Based on the literature examined, the researcher concludes that the Mindfulness practice taught by the Buddha and preserved by the Sangha has evolved into a secularized practice popularized by laypeople with distinct objectives. Western Mindfulness practice, particularly as developed by Jack Kornfield and John Kabat-Zinn, does not aim for spiritual transformation but rather focuses on worldly achievements, primarily the reduction of anxiety and stress for individuals living in the modern age.